Penyuluhan dan Edukasi tentang Kelembagaan pada Proses Pengelolaan Limbah Kotoran Hewan bagi Anggota Koperasi Serba Usaha Karya Nugraha Jaya (KSU KKS) di Kelurahan Cipari Kecamatan Cigugur - Muliawaty, Lia; Ruyani, Nyi Raden (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This community service program (PKM) addresses the suboptimal management of dairy cattle manure (kohe) in Cipari Village, Cigugur District, Kuningan Regency, despite its significant dairy cattle population (approximately 8,000 head) and supportive local government policies. Unmanaged kohe leads to environmental pollution, foul odors, and disease vectors, causing community complaints. Many livestock farmers lack effective waste management systems like composting or biogas. This PKM aims to bridge the gap between existing strong local policies and their on-the-ground implementation, by focusing on "extension and education" and "institutional aspects". It facilitates understanding among members of the Karya Nugraha Jaya Multipurpose Cooperative (KSU KKS) regarding the negative impacts of unmanaged kohe, its economic and environmental potential, and various successful management innovations from institutions like ITB, UGM, Poliban, and BRIN. The program emphasizes the central role of KSU KKS in coordinating waste management and fostering collaboration among stakeholders. Through interactive discussions, case studies, and the formation of task forces for small-scale implementation, the PKM seeks to enhance knowledge, shift attitudes, and strengthen the institutional capacity of KSU KKS to collectively adopt and sustain better waste management practices. The descriptive qualitative research approach, utilizing field observations, in-depth interviews with key informants, and TOWS analysis, provides a holistic understanding of policy innovation and institutional dynamics. The success of this PKM is measured by the increased understanding and the internalization of innovative policies, implementation barriers, and effective strategies by KSU KKS members, translating this knowledge into improved collective practices and institutional strengthening in waste management. This initiative transforms a waste problem into an economic and ecological opportunity, promoting sustainable and independent solutions.